A 45-year high-resolution wave hindcast for the Fijian archipelago: mean climate, spectral characteristics, and long-term trends - Lency Royce Muna; Antonio Espejo; Moritz Wandres; Alexandre Ganachaud; Awnesh Singh; Pascal Dumas; Hervé Damlamian (Ocean Dynamics, 2026)

Assessing responses of reef island seabirds to environmental and anthropogenic drivers - Tristan Berr; Alexandre Millon; Pascal Dumas; Poetea Guehenneuc; Fany Perez; Hélène De Méringo; Julien Baudat‐Franceschi; Éric Vidal (Conservation Biology, 2026)
Tropical insular ecosystems face escalating, cumulative impacts of land‐ and sea‐based ecological threats that jeopardize the long‐term sustainability of their native communities. This joint vulnerability is epitomized by reef island seabirds, which are exposed to reef decline and coastal erosion driven by climate change, reduction in prey availability, human disturbance, and predation by invasive non‐native species. Using site monitoring data acquired from 2000 to 2023, we investigated drivers of species presence and abundance for 15 seabird species (nine Laridae, three Sulidae, two Fregatidae, and one Procellariidae) on 100 coral reef islands around New Caledonia, South Pacific. We established presence and abundance estimates using a compendium of 2805 observations and tested the relative influence of onsite breeding habitat area, characteristics of neighboring marine environments, human visitation, and rodent presence. Responses to ecological drivers varied across species and highlighted distinct functional and taxonomic groups. The presence and abundance of pelagic‐feeding species with high site fidelity were predominantly determined by the availability of breeding habitat, whereas the presence of coastal foragers, including most gulls and terns, appeared constrained by resource availability near breeding sites. Human disturbance had a significant negative influence on the presence of brown noddy ( Anous stolidus ; [−3.41; −1.20]), masked ( Sula dactylatra ; [−3.85; −1.21]), and brown ( Sula leucogaster ; [−4.57; −1.46]) and red‐footed booby ( Sula sula ; [−9.58; −1.20]) and a significant positive influence on the abundance of the commensal silver gull ( Larus novaehollandiae ; [0.03; 0.09]). Our results emphasize the importance of habitat restoration and mitigation of human disturbance for preserving breeding sites of pelagic‐feeding species. However, it may be difficult to sustain populations of coastal seabirds whose presence is mostly driven by small‐scale prey distribution. Thus, a comprehensive approach that fully considers the functional diversity of target seabird communities is needed.

Fish trade and distribution from Vanuatu’s community-based fisheries - Jeremie Kaltavara; Neil Andrew; Tom Brewer; Pascal Dumas; Dirk Steenbergen (Marine Policy, 2026)

Giant clam gardens: Cultural practices and ecological implications for population resilience in New Caledonia - Pascal Dumas; Cecile Portes; Christophe Peignon (Ocean & Coastal Management, 2026)

The role of barrier reef protection to storm surge during tropical cyclones in a narrow lagoon, New Caledonia, south west Pacific - Maxime Duphil; Jérôme Lefèvre; Swen Jullien; Jean Roger; Pascal Dumas; Romain Le Gendre; Jérôme Aucan; Myriam Vendé-Leclerc; Martin Bénébig; Christophe Menkes (Continental Shelf Research, 2025)

Which Method for Which Purpose? A Comparison of Line Intercept Transect and Underwater Photogrammetry Methods for Coral Reef Surveys - Isabel Urbina-Barreto; Rémi Garnier; Simon Elise; Romain Pinel; Pascal Dumas; Vincent Mahamadaly; Mathilde Facon; Sophie Bureau; Christophe Peignon; Jean-Pascal Quod; Eric Dutrieux; Lucie Penin; et al. (Frontiers in Marine Science, 2021)
The choice of ecological monitoring methods and descriptors determines the effectiveness of a program designed to assess the state of coral reef ecosystems. Here, we comparer the relative performance of the traditional Line Intercept Transect (LIT) method with three methods derived from underwater photogrammetry: LIT on orthomosaics, photoquadrats from orthomosaics, and surface analyses on orthomosaics. The data were acquired at Reunion Island on five outer reef slopes and two coral communities on underwater lava-flows. Coral cover was estimated in situ using the LIT method and with LITs and photoquadrats digitized on orthomosaic. Surface analyses were done on the same orthomosaics. Structural complexity of the surveyed sites was calculated from digital elevation models using three physical descriptors (fractal dimension, slope, surface complexity), and used to explore their possible influence in coral cover estimates. We also compared the methods in terms of scientific outputs, the human expertise and time required. Coral cover estimates obtained with in situ LITs were higher than those obtained with digitized LITs and photoquadrats. Surfaces analyses on orthomosaics yielded the lowest but most the precise cover estimates (i.e., lowest sample dispersion). Sites with the highest coral cover also had the highest structural complexity. Finally, when we added scientific outputs, and requirements for human expertise and time to our comparisons between methods, we found that surface analysis on the orthomosaics was the most efficient method. Photoquadrats were more time-consuming than both in situ and digitized LITs, even though they provided coral cover estimates similar to those of digitized LITs and yielded more than one descriptor. The LIT in situ method remains the least time-consuming and most effective for species-level taxonomic identifications but is the most limited method in terms of data outputs and representativeness of the ecosystem.

Seasonal and Interannual Variability of the CO2 System in the Eastern Mediterranean Sea: A Case Study in the North Western Levantine Basin - Cathy Wimart-Rousseau; Thibaut Wagener; Marta Álvarez; Thierry Moutin; Marine Fourrier; Laurent Coppola; Laure Niclas-Chirurgien; Patrick Raimbault; Fabrizio D’Ortenzio; Xavier Durrieu de Madron; Vincent Taillandier; Franck Dumas; et al. (Frontiers in Marine Science, 2021)
The seasonal variability of the carbonate system in the eastern Mediterranean Sea (EMed) was investigated based on discrete total alkalinity (A T ), total dissolved inorganic carbon (C T ), and pH measurements collected during three cruises around Crete between June 2018 and March 2019. This study presents a detailed description of this new carbonate chemistry dataset in the eastern Mediterranean Sea. We show that the North Western Levantine Basin (NWLB) is unique in terms of range of A T variation vs. C T variation in the upper water column over an annual cycle. The reasons for this singularity of the NWLB can be explained by the interplay between strong evaporation and the concomitant consumption of C T by autotrophic processes. The high range of A T variations, combined to temperature changes, has a strong impact on the variability of the seawater p CO 2 ( p CO 2 S W ). Based on Argo float data, an entire annual cycle for p CO 2 S W in the NWLB has been reconstructed in order to estimate the temporal sequence of the potential “source” and “sink” of atmospheric CO 2 . By combining this dataset with previous observations in the NWLB, this study shows a significant ocean acidification and a decrease in the oceanic surface pH T 25 of −0.0024 ± 0.0004 pH T 25 units.a –1 . The changes in the carbonate system are driven by the increase of atmospheric CO 2 but also by unexplained temporal changes in the surface A T content. If we consider that the EMed will, in the future, encounter longer, more intense and warmer summer seasons, this study proposes some perspectives on the carbonate system functioning of the “future” EMed.

Mutations in aARS genes revealed by targeted next-generation sequencing in patients with mitochondrial diseases - Rahma Felhi; Majida Charif; Lamia Sfaihi; Emna Mkaouar-Rebai; Valerie Desquiret-Dumas; Rim Kallel; Céline Bris; David Goudenège; Agnès Guichet; Dominique Bonneau; Vincent Procaccio; Pascal Reynier; et al. (Molecular Biology Reports, 2020)

Influence of PAHs among other coastal environmental variables on total and PAH-degrading bacterial communities - Caroline Sauret; Marc Tedetti; Catherine Guigue; Chloé Dumas; Raphaël Lami; Mireille Pujo-Pay; Pascal Conan; Madeleine Goutx; Jean-François Ghiglione (Environmental Science and Pollution Research, 2016)

Isolation and characterization of fifteen microsatellite loci for the giant clam Tridacna maxima - Daphné Grulois; Josina Tiavouane; Pascal Paul Dumas; Cécile Fauvelot (Conservation Genetics Resources, 2015)

Isolation and characterization of fifteen microsatellite loci for the giant clam Hippopus hippopus (family Tridacnidae) - Josina Tiavouane; Théa Jacob; Pascal Paul Dumas; Cécile Fauvelot (Conservation Genetics Resources, 2014)

Coral assemblages in Tonga: spatial patterns, replenishment capacities, and implications for conservation strategies - Mehdi Adjeroud; Marine J. Briand; Mohsen Kayal; Pascal Dumas (Environmental Monitoring and Assessment, 2013)

Celecoxib but not the combination of celecoxib+atorvastatin prevents the development of monocrotaline-induced pulmonary hypertension in the rat - Zo Rakotoniaina; Pascal Guerard; Frédéric Lirussi; Luc Rochette; Monique Dumas; Françoise Goirand; Marc Bardou (Naunyn-Schmiedeberg's Archives of Pharmacology, 2008)

The protective effect of HMG-CoA reductase inhibitors against monocrotaline-induced pulmonary hypertension in the rat might not be a class effect: comparison of pravastatin and atorvastatin - Zo Rakotoniaina; Pascal Guerard; Frederic Lirussi; Françoise Goirand; Luc Rochette; Monique Dumas; Marc Bardou (Naunyn-Schmiedeberg's Archives of Pharmacology, 2006)

The HMG-CoA reductase inhibitor, pravastatin, prevents the development of monocrotaline-induced pulmonary hypertension in the rat through reduction of endothelial cell apoptosis and overexpression of eNOS - Pascal Guerard; Zo Rakotoniaina; Françoise Goirand; Luc Rochette; Monique Dumas; Frederic Lirussi; Marc Bardou (Naunyn-Schmiedeberg's Archives of Pharmacology, 2006)

Stability of interstitial crustacean communities in an isolated alluvial aquifer - Pascal Dumas (Hydrobiologia, 2002)